2019
DOI: 10.1136/bmjopen-2018-027496
|View full text |Cite
|
Sign up to set email alerts
|

Working with women who use force: a feasibility study protocol of the Positive (+)SHIFT group work programme in Australia

Abstract: IntroductionThis study assesses the feasibility of the Positive Shift (+SHIFT) programme in the context of legal responses and social welfare provision in the state of Victoria, Australia.The +SHIFT programme, adapted from the Vista curriculum, is a group work and case management programme for women who use force. Building on traditional survivor support group strengths, the programme facilitates participants’ engagement with viable alternatives to force while promoting healing. The study also aims to increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…While this is an important question, it has also become clear from different parts of the service system (e.g., women's services, family services, child protection, and substance misuse services) that some women do use force, whether in self-defense or proactively in their family relationships. It has also emerged that most of this use of force does not occur in the same context, or with the same motivation or intent, as men's violence and coercive control of women in their domestic relationships (Kertesz et al, 2019). Both evidence and practice experience suggest that this group of women need a service which addresses both victimization and use of force, and differs significantly from MBC programs.…”
Section: Gender Equivalence and Misidentification In Australiamentioning
confidence: 99%
See 2 more Smart Citations
“…While this is an important question, it has also become clear from different parts of the service system (e.g., women's services, family services, child protection, and substance misuse services) that some women do use force, whether in self-defense or proactively in their family relationships. It has also emerged that most of this use of force does not occur in the same context, or with the same motivation or intent, as men's violence and coercive control of women in their domestic relationships (Kertesz et al, 2019). Both evidence and practice experience suggest that this group of women need a service which addresses both victimization and use of force, and differs significantly from MBC programs.…”
Section: Gender Equivalence and Misidentification In Australiamentioning
confidence: 99%
“…Most women reported that they experienced mental health problems and almost all had experienced partner abuse at some time in their lives. The following discussion of women's experiences, differing social identities, and systems responses to those differences, is drawn from the published program evaluation (Kertesz et al, 2020).…”
Section: Legal Developments That Challenge the Binary: Us And Australiamentioning
confidence: 99%
See 1 more Smart Citation